2006
DOI: 10.1262/jrd.17072
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Ovarian Follicular Development by Injecting Vascular Endothelial Growth Factor (VEGF) and Growth Differentiation Factor 9 (GDF-9) Genes

Abstract: Abstract. Ovarian follicular development in mammals is the complex process including endocrine, paracrine and autocrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…One of the main properties of VEGF is prevention of apoptosis and inflammation (Jung Won Jeona et al 2014). Results of the present research are similar to those of a previous study that has demonstrated VEGF injection to the ovary caused angiogenesis, which reduces ischemia and prevents apoptosis (Shimizu 2006). In this research, a higher dosage of VEGF was shown to be the most effective to induce angiogenesis and to prevent apoptosis in transplanted tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One of the main properties of VEGF is prevention of apoptosis and inflammation (Jung Won Jeona et al 2014). Results of the present research are similar to those of a previous study that has demonstrated VEGF injection to the ovary caused angiogenesis, which reduces ischemia and prevents apoptosis (Shimizu 2006). In this research, a higher dosage of VEGF was shown to be the most effective to induce angiogenesis and to prevent apoptosis in transplanted tissue.…”
Section: Discussionsupporting
confidence: 89%
“…VEGF as an angiogenic factor decreases ischemia and prolongs the graft functionality that helps to keep normal follicular population in whole transplanted mouse ovary. Results of this research confirm previous researches about positive effects of VEGF on function transplanted ovaries (Shimizu 2006;Labied et al 2013). However, the effect of VEGF on transplantation of whole mouse ovary on gluteal muscle was evaluated.…”
Section: Discussionsupporting
confidence: 87%
“…The importance of VEGFA, KDR, and FLT1 in biological processes such as embryogenesis (Carmeliet et al 1996), folliculogenesis (Shimizu 2006), and seminiferous cord formation in the embryonic testis (Bott et al 2006) has been demonstrated. An increasing number of reports suggest that VEGFA has direct effects on nonvascular cells including neuronal cells (Marti & Risau 1998, Wada et al 2006, Nishijima et al 2007), muscle cells (Germani et al 2003, Bryan et al 2008, and granulosa cells (Greenaway et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the vascular endothelial growth factor A (VEGFA) seems to play a major role in ovarian angiogenesis as demonstrated recently by several pieces of evidence (Wulff et al 2001, Zimmermann et al 2003, Kaczmarek et al 2005, Shimizu & Sato 2005, Abramovich et al 2006, Shimizu 2006. Even if relevant progress has been made in understanding the mechanisms involved in the angiogenic events during the dominant final phase of tertiary follicle development (Fraser 2006, Martelli et al 2006, the role of blood vessel remodelling in early follicular stages is unclear.…”
Section: Introductionmentioning
confidence: 99%